2018
DOI: 10.1093/molbev/msy246
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropy Modulates the Efficacy of Selection inDrosophila melanogaster

Abstract: Pleiotropy is the well-established idea that a single mutation affects multiple phenotypes. If a mutation has opposite effects on fitness when expressed in different contexts, then genetic conflict arises. Pleiotropic conflict is expected to reduce the efficacy of selection by limiting the fixation of beneficial mutations through adaptation, and the removal of deleterious mutations through purifying selection. Although this has been widely discussed, in particular in the context of a putative “gender load,” it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(76 citation statements)
references
References 117 publications
(166 reference statements)
4
68
4
Order By: Relevance
“…Thus, tissue-specific genes are more likely to be under positive selection than housekeeping genes. Because nonsynonymous mutations in housekeeping genes have a higher chance to disrupt multiple phenotypes, our findings support that pleiotropic effect is a key determinant of adaptive evolution [17].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, tissue-specific genes are more likely to be under positive selection than housekeeping genes. Because nonsynonymous mutations in housekeeping genes have a higher chance to disrupt multiple phenotypes, our findings support that pleiotropic effect is a key determinant of adaptive evolution [17].…”
Section: Discussionsupporting
confidence: 71%
“…Using this pooling strategy, previous studies have identified numerous genomic features associated with positive selection, including local mutation rate [13][14][15], local recombination rate [13,14,16], gene expression specificity [17], residue exposure to solvent [18], protein disorder [19], virus-host interaction [12,20], protein-protein interaction (PPI) degree [21], X linkage [22][23][24], and sex-biased expression [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In this study a negative correlation between ω and exon length (r 2 = 0.08, P < 0.001) was observed (Additional file 2: Figure S22). These interactions between residues of a protein, commonly refer to as Hill-Robertson interference [62], have a tendency to buffer against the accumulation of amino acid substitutions and can explain a significant portion of the pattern of molecular evolution in genomes [63].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless we observed a clear negative relationship across the four D. mojavensis genomes between transcriptional level and ω. In addition to overall expression, both tissue and sex-bias expression have been known shape the evolutionary trajectories of genes [63, 6971]. Male, or more specifically testes expressed genes have been associated with elevated rates of molecular evolution in Drosophila and across many taxa [72].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that both positive and negative selection are common in coding and some noncoding regions in several model systems, e.g. Drosophila (Andolfatto 2005;Haddrill et al 2008;Fraïsse et al 2019), humans (Torgerson et al 2009;Lindblad-Toh et al 2011;Arbiza et al 2013), and mice (Halligan Det al 2010;Kousathanas et al 2011). It has been suggested that the majority of adaptive evolution may occur in noncoding, regulatory regions, because new mutations that occur in these regions may have fewer deleterious pleiotropic effects (Carroll 2005;Wray 2007).…”
Section: Introductionmentioning
confidence: 99%